2014
DOI: 10.1007/s00737-014-0440-9
|View full text |Cite
|
Sign up to set email alerts
|

Are women with a history of abuse more vulnerable to perinatal depressive symptoms? A systematic review

Abstract: The objective of this paper is to examine the association between maternal lifetime abuse and perinatal depressive symptoms. Papers included in this review were identified through electronic searches of the following databases: Pubmed Medline and Ovid, EMBASE, PsycINFO, and the Cochrane Library. Each database was searched from its start date through 1 September 2011. Keywords such as "postpartum," "perinatal," "prenatal," "depression," "violence," "child abuse," and "partner abuse" were included in the purview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 89 publications
10
68
1
4
Order By: Relevance
“…The association between postpartum depression and abuse was significant in developed countries but not in developing countries. However, a systematic review found positive association between maternal abuse and postpartum depressive symptoms (Alvarez-Segura et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The association between postpartum depression and abuse was significant in developed countries but not in developing countries. However, a systematic review found positive association between maternal abuse and postpartum depressive symptoms (Alvarez-Segura et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Women who have experienced various forms of abuse (e.g. abuse in childhood, experience of intimate partner violence) are a group with a particularly high risk of depression or anxiety during pregnancy [44]. Between 1.8 and 31.7 % of pregnant women are victims of violence, although the number of unrecorded cases is likely to be far higher [138].…”
Section: Correlates Of Depression and Anxiety In Pregnancymentioning
confidence: 99%
“…Although there have been several reviews on prenatal and postpartum depression (Varkukla et al 2009; Patel et al 2012; Sockol et al 2013), and some reviews on the relationship between a maternal history of abuse and risk of prenatal or postpartum depression (Beydoun et al 2012; Alvarez-Segura et al 2014), to the best of our knowledge, no detailed systematic review has summarized or quantified the relationship between maternal history of CSA and depression or depressive symptoms during the prenatal and postpartum periods. Given this gap in the literature, and the high prevalence of history of early life sexual abuse (Andrews et al 2004) and depression among women (Kessler et al 1994), we undertook this systematic review and meta-analysis so as to summarize the literature concerning history of CSA with depression and depressive symptoms in pregnant and postpartum women.…”
Section: Introductionmentioning
confidence: 99%